ANALISIS LAPORAN KEUANGAN PADA BANK PERKREDITAN RAKYAT (BPR) BEPEDE KS CABANG BERAU DI TANJUNG REDEB - MUNAWAROH, SITI (ACCOUNTING STUDY PROGRAM, STIE MUHAMMADIYAH TANJUNG REDEB, 2017)
ABSTRACT The purpose of this research is to know the level of liquidity, solvency and rentability of BPR BePeDe KS Berau branch in Tanjung Redeb period 2015 - 2016. The analysis tool used is financial ratio analysis, namely: liquidity ratio, solvency ratio and rentability ratio. The result of the research shows that based on the overall liquidity ratio of BPR BePeDe KS Berau branch in the healthy category. During the Year 2015 to 2016 BPR BePeDe Bers Berau branch financial condition based on overall solvency ratio is quite healthy. During 2015 to 2016 the financial condition of BPR BePeDe KS branch of Berau is not well seen from the ratio of profitability, which is shown by net profit margin and gross yield on total assets which still decrease. In this case the effectiveness of BPR BePeDe KS management of Berau branch in managing its assets to generate a declining profit, although there is a relatively small increase in grossprofit margin.